The impact of the training modules on the pliometric training on the explosive force of the lower limbs of the volley ball players. - hakim.ghellab,; boukratem belkacem, (sports creativity, 2025)
This study aims to identify the impact of the training units on the explosive force of the lower limbs of the volley ball players under 19 years , the study community included all the teams of state of m’sila volley ball class of the middle and. The sample of the research consisted of the 10 players of the sport’s star of m’sila which represents the controlling sample in the research, and the 10 m’sila youth volley ball .team that consists of 10 players which represents the experimental group . The researchers used the experimental approach because it fits and it is suitable for the research method which is the application of the pliometric exercises in field on the research sample , in order to know the results the researchers used the physical test which are long jump test of stability . The study found positive effect of pliometric exercises on the development of explosive force in volley ball players under 19 years this effect is represented. By the statistical differences in the pre and post test of the experimental group and the statistically significant differences between the control group , and the experimental in the pre tests for both tests.